Corporate Social Responsibility – How to Change the Attitude of the Top Management from Image to Real – A Case Study of a Listed Company - Tomasz URBANCZYK (Communications of International Proceedings, 2020)
The purpose of this article is to take up the discussion about how to change the unethical behaviors of top management in relation to corporate social responsibility (CSR). The research is based on a case study of a company listed on the Polish Stock Exchange (SE) on the Respect Index (RI) of socially responsible companies. The analysis was carried out on the basis of an in-depth interview with selected still working as well as former employees of a listed company. The case study reveals that CSR may only be of an image-related nature. It shows the lack of consistency of the declared values in CSR reports with the unethical behavior of the company's management towards its employees. The author proposes a concept in which SE authorities would extend the scope of their activities to preventive and intervention measures. Preventive actions would concern (1) top management education in relation to the impact of ethical behavior and positive relationships on the company's results; (2) implementation of 360 degree feedback. Intervention, in turn, would relate to (3) whistleblowing.
Keywords: CSR; Ethics; Positive Relations; 360 Degree Feedback; Whistleblowing.